The Potential of Hydro Energy as the Renewable Energy Alternatives in the Rural Area - Kelanit Florence Rutselin; Dani Wijaya; Muhammad Ridwan; Adi Gunawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2024)
Hydro energy systems are broadly used around the world as renewable energy. The concept of hydro energy becomes the major energy alternative for fulfilling the energy demand, especially in the remotes area. The type of micro-hydro power was the most applicable to meet electricity purposes. Micro hydropower system proposes an environment friendly used because of easy to operate and low operation cost, especially in the area which high water availability. This review paper focuses on the potential of hydro energy systems that are built in remote areas. This review revealed three types of hydropower systems, namely mini-hydropower, small hydro power, and micro hydro power. Out of these three types, micro hydro power can become the solution for electrification in remote areas. Micro hydro power installation was built with many types of technological approaches. Nevertheless, considering geographical purposes, the capacity of energy production, and sustainability of resources. Yet, several obstacles should be aware of such as power availability in remote areas. The technical issue and government support become the key to success in applying hydropower in the site of installation. Otherwise, conventional fossil fuel-based systems which are costly and unsustainable may require due to the operating system of micro-hydro power as well